FEATURES IN THE STRUCTURE OF THE LIMBS OF TRAGOCERINE FROM THE ‘’GOOSE FLIGHT’’ SITE IN NORTHEASTERN KAZAKHSTAN - AINAGUL SHARIPOVA; NAZYMGUL AKIMBEKOVA (Research Retrieval and Academic Letters, 2026)
The study of the limb skeletons of ancient ungulates, along with the study of their skulls and teeth, is of great importance for reconstructing the course of their evolution and the landscapes of the past. This significance is particularly high, as changes in the locomotor apparatus play a major role in the progressive evolution of animals (Zenkevich, 1944; Beklemishev, 1964). It has been noted (Lukin, 1964) that following the nervous system, the system of locomotor organs changes most rapidly in evolution. Ancient ungulates, especially the highly organized groups of the order Artiodactyla, represent one of the most indicative objects of study. Among them, the main place belongs to ruminants. K.K. Flerov (1962) notes that ruminants much better reflect the smallest changes in the landscape in the structure of their adaptations than, for example, carnivores. This is fully applicable to the background groups of late Neogene ruminants – Lagomeryx, deer, Paleotragus giraffes, gazelle-like antelopes, and tragocerins. E.L. Korotkevich points out that when addressing these issues, the inequality of morphological traits should be taken into account. In the presence of remains of two closely related genera of tragocerins in a burial, the separation of the bones of their postcranial skeleton is very difficult and to some extent conditional.